Magnetism: Entanglement, Konke and the Magnet as Discrete - Bhekuzulu Khumalo (JOURNAL OF ADVANCES IN PHYSICS, 2020)
Understanding that everything is in a relationship led us to ask what then is the relationship that caused particles to be. Our investigation led us to understand that all particles are made up of the same stuff we called konke, Something that has experimental backing. Understanding that this konke must get into relationships so that we get particles, we have a chance to look at particles from what they are made off understanding. It is how much of konke that gives a particle mass and its categorization. What is the nature of magnetism from the viewpoint that all things are made of the same stuff, konke. Two simple experiments are requiring a vacuum that will help solve the nature of magnetism, which should end up as a discrete phenomenon, like all other phenomena. Rely on experimentation as much as possible.